2017
DOI: 10.1369/0022155417718541
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of Picrosirius Red Multiplexed With Immunohistochemistry for the Quantitative Assessment of Collagen in Tissue Sections

Abstract: The low cost and simplicity of picrosirius red (PSR) staining have driven its popularity for collagen detection in tissue sections. We extended the versatility of this method by using fluorescent imaging to detect the PSR signal and applying automated quantification tools. We also developed the first PSR protocol that is fully compatible with multiplex immunostaining, making it possible to test whether collagen structure differs across immunohistochemically labeled regions of the tissue landscape. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 45 publications
1
86
0
1
Order By: Relevance
“…Tissue was paraffin-embedded, sectioned, and stained with hematoxylin and eosin (H&E) or Masson's trichrome by the Experimental Animal Pathology Laboratory (Carbone Cancer Center, University of Wisconsin-Madison; Madison, WI, USA). Picrosirius red staining was completed as described [47]. Immunofluorescence was performed as described [103].…”
Section: Histology and Immunofluorescencementioning
confidence: 99%
“…Tissue was paraffin-embedded, sectioned, and stained with hematoxylin and eosin (H&E) or Masson's trichrome by the Experimental Animal Pathology Laboratory (Carbone Cancer Center, University of Wisconsin-Madison; Madison, WI, USA). Picrosirius red staining was completed as described [47]. Immunofluorescence was performed as described [103].…”
Section: Histology and Immunofluorescencementioning
confidence: 99%
“…In addition to polarized light, picrosirius red staining can also be visualized with fluorescence microscopy, which is more sensitive, but does not show differences in fiber thicknesses (Wegner et al, ).…”
Section: Techniques To Analyze Collagenmentioning
confidence: 99%
“…Wegner et al, [27] performed a study with fluorescencent PSR in prostate of C57BL/6J mice. They found that fluorescent PSR imaging was more sensitive than polarized light for identify the collagen fibers.…”
Section: Discussionmentioning
confidence: 99%